A Correlational Study of Effort Reward Imbalance (ERI) and Job Satisfaction among Employees Working in Banking Sector of Pakistan - Zafar Ahmad, Naureen Munir, Shazia Shahzadi (Pakistan Journal of Medical & Health Sciences, 2022)
The research was carried out to investigate the relationship of Effort Reward Imbalance (ERI) with Job Satisfaction of employees, working in banking sector. For this purpose the ERI questionnaire (Siegrist,1996) and Job Satisfaction Survey (Spector, 1994) were used for measurement. The cross-sectional survey with purposive convenient sampling technique was used for data collection. The sample was consisted of 209 employees comprised of 149 male and 60 female employees working in different banks. 62.2% employees age ranging from 20-30, 25.8% from 31-40, 12% from 41-50. 71.3%were male and 28.7% were female. 9.1 % participants intermediate 43.5 % were a graduate 47.4 % were postgraduate. 59.8 % employees have 1-5 years of job tenure. 22.5% have 5 -10 years of job tenure 9.6% have 10-15 years of job tenure 4. 3% have 15-20 years of job tenure and 3.8% have 20-25 years of job tenure. The results revealed that effort reward imbalance and job satisfaction are correlated whereas gender has no significant impact with ERI and Job satisfaction of employees working in banking sector. Keywords: Effort Reward Imbalance, Job Satisfaction, Bank Employees